Ag(I)-catalyzed heterocyclization/[3+2] cycloaddition of α-alkynylenones with β-enaminones: tandem access to highly substituted cyclopenta[c]furans - Vara, Vijay; Thete, Kishor R.; Panikar, Sera Deepu; Khan, Akram A.; Muthukrishnan, M. (Journal of Organic Chemistry, 2025)
A robust Ag(I)-catalyzed tandem heterocyclization/[3 + 2] cycloaddition of alpha-alkynylenones with beta-enaminones was developed, enabling efficient synthesis of cyclopenta[c]furans with good yields, operational simplicity, and broad substrate scope. In addition, it also presents an extended methodology to synthesize unsymmetrical tri(hetero)aryl methane having chromone and furan/pyrrole scaffolds by a slight modification of starting materials. Moreover, the synthesized cyclopenta[c]furans exhibit good fluorescence properties with quantum yields ranging from 0.33 to 0.53, as suggested by the photophysical studies.

Cocrystals of the highly potent sickle cell anemia drug voxelotor with trimesic acid: a substantial enhancement in in vitro dissolution performance at physiological pH - Khan, Akram A.; Shaikh, Tabrez R.; George, Christy P.; Gonnade, Rajesh G. (Crystal Growth & Design, 2025)
Global Blood Therapeutic's (GBT's) Voxelotor is an investigational oral therapy for treating sickle cell anemia. It functions by increasing the affinity between hemoglobin and oxygen, thereby preventing the sickling of red blood cells and altering the disease's pathology. The US FDA has approved Voxelotor for the treatment of sickle cell anemia and granted it an orphan drug status. However, Voxelotor is classified as a BCS class II, indicating poor water solubility. The current study explores the enhancement of Voxelotor's water solubility by forming cocrystals with trimesic acid (TMA). Novel cocrystals, cocrystal solvates, and hydrates of Voxelotor (Vox) with trimesic acid (TMA) have been developed to improve their solubility. The new solids were characterized using PXRD, DSC, TGA, XPS, HSM, and single-crystal X-ray diffraction studies, and the intermolecular interactions were quantified using Hirshfeld surface analysis. Detailed crystallographic analysis revealed strong O-H center dot center dot center dot N hydrogen bonding interactions between Vox and TMA, primarily involving the COOH functional group of TMA and the pyridine or pyrazole groups of Vox. Additionally, TMA molecules participate in further hydrogen bonding-either with themselves or with solvates, including hydrates, through mono- or dimeric O-H center dot center dot center dot O H-bonding synthons. In vitro solubility studies demonstrated a significant increase in the solubility of Voxelotor in the Vox-TMA cocrystals compared to the pristine drug at physicochemical pH 4.5 and 6.8. Stability studies confirmed that the nonsolvated multicomponent crystal retains their structural integrity under nonambient conditions without undergoing polymorphic phase transitions. In contrast, the solvated crystals, including hydrates, undergo phase transitions within the temperature range of 100-130 degrees C, losing solvents and converting into one of the nonsolvated cocrystal forms. These findings suggest that the novel Vox-TMA cocrystals have the potential to enhance the therapeutic performance and clinical utility of Voxelotor.

Phosphine-catalyzed nucleophilic ring opening of cyclopropenones with sulfoximines to access N-α,β-unsaturated acyl sulfoximines - Thete, Kishor R.; Vara, Vijay; Khan, Akram A.; Muthukrishnan, M. (Journal of Organic Chemistry, 2025)
Herein, we describe the formation of biologically relevant N-alpha,beta-unsaturated acyl sulfoximines via phosphine-catalyzed C-C bond activation of cyclopropenones with weakly nucleophilic sulfoximines. The new process does not require a transition metal or external oxidant and displays high regioselectivity and exclusive E-selectivity. Other salient features of the method are a broad substrate scope, high compatibility with various functional groups, and high atom economy.

Synthesis and crystal structure of [Sr(urea)(NO3)2]n - Bektursinova, Aysanem; Djumanazarova, Zulfiya; Uzakbergenova, Zamira; Ashurov, Jamshid; Khan, Akram A.; Kadirova, Shakhnoza; Torambetov, Batirbay (Acta crystallographica Section E, Crystallographic communications, 2025)
The crystal structure of poly[di-μ<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2-nitrato-μ<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2-urea-strontium(II)], [Sr(NO<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">3)<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2(CH<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">4N<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">2O)] <span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">n , was determined using single-crystal X-ray diffraction. Crystallizing in the ortho-rhom-bic space group <i style="box-sizing: inherit; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;">Aba2, the asymmetric unit consists of an Sr<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">II cation, two nitrate anions, and two half urea mol-ecules. The Sr<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">II cation adopts a distorted deca-hedral geometry coordinated by ten oxygen atoms, with Sr-O bond lengths ranging from 2.573 (3) to 2.847 (5) Å. The nitrate anions act as bidentate ligands, displaying both terminal and bridging coordination modes. The structure features a robust coordination network supported by hydrogen bonding. These results provide insight into the coord-ination behaviour of Sr<span style="box-sizing: inherit; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif;">II with nitrate and urea ligands, contributing to the understanding of supra-molecular architectures in metal-organic frameworks (MOFs).

Radical-promoted cyclization of 3-allyl-2-arylquinazolinones mediated by silver(i) salts to access SCF3/SCN-enriched dihydroisoquinolino[1,2-b]quinazolinones - Vara, Vijay; Thete, Kishor R.; Khan, Akram A.; Muthukrishnan, M. (Organic & Biomolecular Chemistry, 2026)
Herein, we describe an efficient approach for the synthesis of SCF3- and SCN-functionalized polycyclic dihydroisoquinolino[1,2-b]quinazolinones through radical-mediated thio-functionalization of allylic alkenes followed by intramolecular cyclization. The transformation proceeds through sulfur-radical-triggered C-S and C-C bond formation, providing an efficient route to sulfur- and fluorine-enriched polycyclic quinazolinones. Moreover, this strategy offers high atom economy, operational simplicity, and broad substrate compatibility.